Color atlas and textbook of diagnostic microbiology (Lippincott, 1997)
Completely revised and updated, the fifth edition reflects a wealth of new findings. Readers will learn to identify those microbial agents associated with infectious disease, and will understand both the basic biochemical and metabolic pathways that serve as the basis for identification, and the microbes that cause disease. An overview of microbiology lays a solid foundation for further areas of study, including taxonomy, classification, identification, and speciation, and explains all major microorganisms and their role as agents in disease. Easy-to-read charts outline theory, procedures and interpretations of tests